2009
DOI: 10.1371/journal.pmed.1000043
|View full text |Cite
|
Sign up to set email alerts
|

Upper-Room Ultraviolet Light and Negative Air Ionization to Prevent Tuberculosis Transmission

Abstract: BackgroundInstitutional tuberculosis (TB) transmission is an important public health problem highlighted by the HIV/AIDS pandemic and the emergence of multidrug- and extensively drug-resistant TB. Effective TB infection control measures are urgently needed. We evaluated the efficacy of upper-room ultraviolet (UV) lights and negative air ionization for preventing airborne TB transmission using a guinea pig air-sampling model to measure the TB infectiousness of ward air.Methods and FindingsFor 535 consecutive da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
152
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 186 publications
(158 citation statements)
references
References 42 publications
0
152
0
3
Order By: Relevance
“…However, of the three technologies available to supplement or replace natural ventilation (at night, for example), germicidal ultraviolet air disinfection holds the greatest potential for sustainable effectiveness. Some studies 472,473 have shown effectiveness under experimental hospital conditions in Peru and South Africa, and recent advances in dosing and fixture technology and maintenance strategies promise wider use of this highly cost-effective intervention-especially as LED technology eventually replaces conventional lowpressure mercury lamps and fixtures, with the potential for solar and battery power.…”
Section: The Lancet Respiratory Medicine Commissionmentioning
confidence: 99%
“…However, of the three technologies available to supplement or replace natural ventilation (at night, for example), germicidal ultraviolet air disinfection holds the greatest potential for sustainable effectiveness. Some studies 472,473 have shown effectiveness under experimental hospital conditions in Peru and South Africa, and recent advances in dosing and fixture technology and maintenance strategies promise wider use of this highly cost-effective intervention-especially as LED technology eventually replaces conventional lowpressure mercury lamps and fixtures, with the potential for solar and battery power.…”
Section: The Lancet Respiratory Medicine Commissionmentioning
confidence: 99%
“…Germicidal ultraviolet upper-room light is also eff ective, but needs electricity and reliable maintenance. 68 Findings from a series of studies in Peru have provided key lessons for interventions to control infection in low-resource settings. 69,70 First, natural ventilation is a low-cost environmental measure for tuberculosis infection control.…”
Section: Infection Control In Health Facilitiesmentioning
confidence: 99%
“…During a 4-yr period, for example, Riley estimated an average concentration of infectious quanta of 1 in 11,000 cf (311 m 3 ) and also calculated that this extremely low average concentration was sufficient to explain the rates of transmission to student nurses in hospitals during the prechemotherapy era (Riley 1957;Riley et al 1962). This same approach, using guinea pigs to quantify infectious quanta, has been used to measure the impact of such interventions as ultraviolet air disinfection, electrostatic precipitators, surgical masks on patients, and, most importantly, effective treatment as discussed below (Escombe et al 2009;Dharmadhikari et al 2012Dharmadhikari et al , 2014.…”
Section: Airborne Mycobacterium Tuberculosismentioning
confidence: 99%
“…Because the entire upper room area is available as an air disinfection chamber, room air turnover rates through the upper room can be high, approaching 60 ACH in a recent study, using commercially available inexpensive ceiling fans. Both room testing and modeling suggest that neither fan velocity nor direction are critical factors, although some fan experts favor downward direction in rooms with high ceilings to avoid lower room stagnation (Escombe et al 2009;Zhu et al 2013Zhu et al , 2014. Low vertical air velocity results in longer but fewer passages of particles through the irradiated zone, whereas with higher vertical air velocities, particle exposure per pass is shorter, but passages are more frequent, with similar net exposure.…”
Section: Upper Room Uvgimentioning
confidence: 99%